2021
DOI: 10.3390/antibiotics10101232
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Drug Resistant Bacteria as Aetiological Factors of Infections in a Tertiary Multidisciplinary Hospital in Poland

Abstract: Global and local initiatives were recently undertaken to reduce the burden of antibiotic resistance. The aim of the study was to describe the incidence and the aetiology of bacterial infections among hospitalized patients with special attention paid to the multidrug resistant (MDR) bacteria. This retrospective study was based on prospectively collected data from 150,529 consecutive patients hospitalized in a tertiary multidisciplinary hospital in the years 2017–2019. All consecutive microbiological tests from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(36 reference statements)
1
0
0
Order By: Relevance
“…According to antibiotype, MDR phenotype was found in 62% of the isolates studied regardless of the guideline used. This percentage aligns with the range reported in other studies involving clinical isolates of Enterobacterales [28,29]. The presence of the MDR phenotype was associated with the main ESBL gene characterized, bla CTX-M-15 .…”
Section: Discussionsupporting
confidence: 89%
“…According to antibiotype, MDR phenotype was found in 62% of the isolates studied regardless of the guideline used. This percentage aligns with the range reported in other studies involving clinical isolates of Enterobacterales [28,29]. The presence of the MDR phenotype was associated with the main ESBL gene characterized, bla CTX-M-15 .…”
Section: Discussionsupporting
confidence: 89%
“…Bacterial isolation was similar in in-hospital and non-hospital infections (53% versus 49%). In total, 28.1% of the organisms detected in the study showed multi-drug resistance, the most common being E. coli ESBL, followed by S. aureus MRSA [38][39][40].…”
Section: Discussionmentioning
confidence: 96%
“…There are a large number of studies reporting MDR pathogens in different parts of the world, which would explain the factors that trigger the increase in epidemic outbreaks, morbidity and mortality, with significant direct and indirect costs (8,10,11,12,15,17,29,34,37,50,62,65,68,87,91). The most frequently reported MDR microorganisms in this last decade were found among isolates of K. pneuomaniae, E. coli, P. aeruginosa, A. baumannii, SARM and VRE.…”
Section: Characteristicsmentioning
confidence: 99%
“…In the last decade, the increase in antimicrobial resistance in ICUs has been reported, mainly due to the spread of these multidrug-resistant (MDR) bacteria (8)(9)(10)(11)(12). MDR is defined as resistance to more than one agent in three or more antimicrobial categories, extensively-drug resistant bacteria (XDR), is defined as non-susceptibility to at least one agent in all but two or fewer antimicrobial categories (i.e., bacterial isolates remain susceptible to only one or two categories), and pan-drug resistant bacteria (PDR) is defined as non-susceptibility to all agents in all antimicrobial categories (9).…”
Section: Introductionmentioning
confidence: 99%